Comparison between the standard average muscle activation wtith the use of snorkel and without snorkel in breakstroke technique - Conceicao, A.; Gamboa, H.; Palma, S.; Araújo, T.; Nunes, N.; Marinho, D.; Costa, A.; Silva, A.; Louro, H. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: In swimming the snorkel (K4b2, Italy, Rome), which consists of a valve train Aquatrainer (Cosmed, Rome, Italy) is often used for analysis of various physiological and biomechanical aspects has allowed researchers to analyze its feability and reliability, as the mechanical constraints caused by this system. Electromyography (EMG) evaluates the neuromuscular activity by plotting the electrical activity of muscle and thus displaying patterns of muscle activation. The purpose of this study was to compare the average pattern of muscle activation in two situations, with and without the use of a snorkel in the breakstroke technique. METHODS: Five male subjects (Mean ± SD: age 19 ± 3,67 years; weight 76.1 ± 6.58 kg; height 178 ± 0.05 cm; fat mass percentage 14,68 ± 1.96; IMC 24 ± 1,66), were subjected to a test consisting of a protocol of 2 x 25m breakstroke, in the first part of the test the swimmers used a snorkel; in the second part they swam without snorkel at 95% of transit time for 200m crawl. Using a wireless signal acquisition system (bioPLUX research, Portugal) and EMG sensors (emgPLUX, Portugal), muscle activity of Biceps Brachii (BB) and Triceps Brachii (TB) of the right arm was recorded throughout the test and synchronized with the video images. The raw EMG was processed offline using Python (version 2.4) routines to compare morphology of the pattern of EMG signal recorded form BB and TB during both test conditions. The signals were subsampled to a frequence of 200Hz, then low-pass filtered with a smoothing window of 50 samples and full-wave rectified. We selected the (middle-700_middle+2300) samples of the raw signal on all identical pathways (15m). For each subject, muscle and test condition, mean, standard deviation, maximum and minimum values of EMG were determined. In order to compare the pattern EMG wave of the swimming movement with and without snorkel, the mean EMG wave was computed for each subject, muscle and test condition. RESULTS: The results demonstrated that the mean activation (EMG) of the BB and TB are higher with the use of snorkel. With respect to the maximal values, higher values in BB were observed both in the muscles recorded as well as in the condition with use of a snorkel. DISCUSSION: We observed in both muscles higher EMG values when using the snorkel. Since BB higher values mean higher activation in both situations. The curve of the EMG signal pattern of the cycle for each muscle group is different from subject to subject, and was different between each situation.